MODEL PENENTUAN RUTE KENDARAAN DENGAN STRATEGI CAMPURAN GUDANG TRANSIT DAN PENGIRIMAN LANGSUNG MEMPERHATIKAN MASALAH JENDELA WAKTU, LIFO, DAN DURASI MAKSIMUM - Nabila, Sarah
The current transportation and distribution system is increasingly becoming the concern of business enterprise who carry out all activities of the company involving the logistics system, because the accuracy of the logistics system is expected to process an enterprise to be efficient and effective. This research tries to develop research on Simultaneous Pickup and Delivery Problems with Cross-docking (PDPCD) which provides direct shipping strategy and transit warehouse or both, the LIFO arrangement is applied in the direct shipping process. If the solution obtained is a pickup and delivery route solution, the arrangement of the pickup and delivery of goods must be arranged according to LIFO restrictions. Model provide three possible solutions which involve the LIFO function in a pickup and delivery strategy. The Simulated Annealing (SA) algorithm developed was able to stabilize and converge to obtain a solution close to the optimal value. The objective function obtained between analytic algorithm and SA has a gap of 7% with a computational time difference of 206,087.06 times faster.